2023
DOI: 10.24072/pcjournal.264
|View full text |Cite
|
Sign up to set email alerts
|

Evolution within a given virulence phenotype (pathotype) is driven by changes in aggressiveness: a case study of French wheat leaf rust populations

Abstract: Evolution within a given virulence phenotype (pathotype) is driven by changes in aggressiveness: a case study of French wheat leaf rust populations , Peer Community Journal, 3: e39.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…In this study, we highlighted a significant difference in aggressiveness between two P. triticina pathogenotypes that not only differed in their genotype but also in their virulence profile, and co-dominated in the varietal landscape during a short time period (2012-2015). This result complements the findings obtained by Fontyn et al (2023), which showed a difference in aggressiveness between ’new’ pathogenotypes and ’old’ ones, all of which had the same virulence profile, over a longer period of time (2006-2016). These two complementary approaches (see Introduction) provide a strong body of evidence attesting to the role of aggressiveness in the domination of certain isolates.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, we highlighted a significant difference in aggressiveness between two P. triticina pathogenotypes that not only differed in their genotype but also in their virulence profile, and co-dominated in the varietal landscape during a short time period (2012-2015). This result complements the findings obtained by Fontyn et al (2023), which showed a difference in aggressiveness between ’new’ pathogenotypes and ’old’ ones, all of which had the same virulence profile, over a longer period of time (2006-2016). These two complementary approaches (see Introduction) provide a strong body of evidence attesting to the role of aggressiveness in the domination of certain isolates.…”
Section: Discussionsupporting
confidence: 89%
“…The pathotyping tests were performed in a greenhouse on eight-day-old wheat seedlings grown in a plastic box containing potting soil placed under standardized conditions as described in Fontyn et al (2023). The inoculation was performed with 10 fresh (two-week-old) spores, picked one by one with a human eyelash under a dissecting microscope, then deposited on a 3 cm-long segment of the second leaf of each seedling, maintained with double-sided tape on a rigid plate coated with aluminum foil.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations